2019
DOI: 10.1029/2019wr024991
|View full text |Cite
|
Sign up to set email alerts
|

Historical Drought Assessment Over the Contiguous United States Using the Generalized Complementary Principle of Evapotranspiration

Abstract: As drought involves diverse natural and human‐made processes in hydrologic cycles, it is necessary to track a process‐specific variable for efficient drought risk management. In this study, we employed a state‐of‐the‐art formulation of the generalized complementary relationship (GCR) to estimate terrestrial evapotranspiration (ET). The GCR ET estimates were used to assess historical droughts over the contiguous United States (CONUS) in relation to long‐term natural fluctuations. Results showed that the GCR pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 116 publications
1
21
0
Order By: Relevance
“…By modifying the definitive derivation of Brutsaert (2015), Szilagyi et al (2017) generalized this principle with a polynomial approximation. The following studies have confirmed the superior performance of the GCR to sophisticated land surface models, reanalysis climate data, and even a state‐of‐the‐art spatial interpolation of flux observations (D. Kim et al, 2019; Ma & Szilagyi, 2019; Ma et al, 2019). More details about the GCR are given in Szilagyi et al (2017).…”
Section: Methodsmentioning
confidence: 74%
“…By modifying the definitive derivation of Brutsaert (2015), Szilagyi et al (2017) generalized this principle with a polynomial approximation. The following studies have confirmed the superior performance of the GCR to sophisticated land surface models, reanalysis climate data, and even a state‐of‐the‐art spatial interpolation of flux observations (D. Kim et al, 2019; Ma & Szilagyi, 2019; Ma et al, 2019). More details about the GCR are given in Szilagyi et al (2017).…”
Section: Methodsmentioning
confidence: 74%
“…The timescale for summing ET and E p depends on users' interests. We chose the 12‐months timescale, because vegetation conditions tend to be correlated strongly with SEDI at 9‐months or longer timescales (Kim, Lee, et al., 2019). As recommended by Vicente‐Serrano et al.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The timescale for summing ET and E p depends on users' interests. We chose the 12-months timescale, because vegetation conditions tend to be correlated strongly with SEDI at 9-months or longer timescales (Kim, Lee, et al, 2019). As recommended by Vicente-Serrano et al (2018), the cumulative probability F[•] was calculated with 3-parameter log-logistic (LL3) distributions and the probability weighted method.…”
Section: Drought Assessment With New Climate Projectionsmentioning
confidence: 99%
See 2 more Smart Citations